Osteoporosis: A preventable silent killer but not well addressed (Bangladesh Medical Journal, 2016)
Osteoporosis is characterized by low bone density, micro-architectural deterioration of the bone tissue, enhanced bone fragility and increasing susceptibility to fracture. Osteoporosis is an important public health problem leading to an increased risk of developing spontaneous and traumatic fractures. It is a silent disease until it is complicated by fractures that can occur following minimal trauma. These fractures are common and place an enormous medical and personal burden on individuals during aging and a major economic toll on the nation. To reduce the burden high-risk patients must be identified, evaluated for factors contributing to skeletal fragility, and should be treated to reduce fracture risk. Osteoporosis is a preventable disease and can be diagnosed and treated before any fracture occurs. Importantly, even after the first fracture has occurred, there are effective treatments to decrease the risk of further fractures. Both Pharmacologic and non- pharmacological interventions can reduce the risk for fracture in appropriately selected patients, with a generally favorable safety profile.Bangladesh Med J. 2016 May; 45 (2): 101-109